An analysis of the labour market and its policy of Bangladesh - Yasmin, Sanoara; Rabbanee, Fazlul Kabir; Haque, A. K. M. Ahasanul (SatyaDham Foundation, 2012)
Labor market policy is significant for a country’s higher investment and economic growth. The labor forces of Bangladesh are splited in different sectors like agriculture, industry, service sectors, foreign wage earners, etc. But the labor market of Bangladesh is suffering from different types of problems like wage discriminations, existence of child labor, lack of workforce security, lack of updated information, lack of technology, and so forth. This paper is an attempt to highlight different issues and problems of Bangladesh labor market. It also focuses on the analysis of the labor market and the contribution of different sectors in national GNP. The paper also pinpoints on the different problems of Bangladeshi wage earners in foreign countries, their remittance and their contribution in national GNP. Finally, the paper attempts to recommend some policy measures to handle the pertaining problems of different sectors and for the smooth development of the same.